Implementasi Sistem Informasi Sumber Daya Manusia dalam Kegiatan Rekruitmen Karyawan : (Studi Pada Warung Makan Bebek Songkem Pak Salim) - Nasim Nasim; Nur Aini; Iwanussholeh Iwanussholeh; Iriani Ismail (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the process of the human resources information system in implementing employee recruitment which is implemented at the Bebek Songkem Pak Salim food stall so that it can reduce the occurrence of irregularities and improve employee performance. The type of research used is descriptive-qualitative research. The focus of this research is the human resources information system in employee recruitment. In this research, procedures for collecting, interviewing, storing, maintaining, processing and grouping data required by an organization. The results of this research show that to keep up with the development of information systems that are useful for the progress of food stalls, quality human resources are needed taking into account knowledge, skills and abilities. Advances in information technology cannot run well without being supported by reliable quality human resources. Bebek Songkem Pak Salim's food stall operates in the culinary sector. If another food stall asks for new workers from Bebek Songkem Pak Salim's food stall, a procedure will be created to determine the workforce that meets the standards of the requested food stall. Applicants or prospective employees take part in the selection carried out by Pak Salim's Bebek Songkem food stall in accordance with the flowchart applied by the food stall, especially external food stalls. Human resource capabilities with information technology can create food stalls that can compete with other food stalls, so that in practice food stalls will look for quality workers.